The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.21273/jashs.128.5.0636
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Effects on Dormancy Completion of Vegetative Buds in Apple

Abstract: The relative contribution of various temperatures to dormancy completion of lateral vegetative apple [Malus sylvestris (L.) Mill. var. domestica (Borkh.) Mansf.] buds was studied quantitatively on whole container-grown trees. Trees were exposed continuously to 10 different temperatures and also to daily alternating temperatures in a 24-hour cycle. In addition, fully chilled vertically and horizontally positioned shoots were compared under forcing co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
35
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(46 citation statements)
references
References 21 publications
10
35
0
1
Order By: Relevance
“…However, axillary buds generally developed close to the vegetative buds, and the vertical shoots became less mature than the horizontal and inclined shoots, and so had fewer flowering buds. These observations are consistent with those of Hampson et al (2004), Ito et al (1999), Meilan (1997), and Naor et al (2003). Inclined shoots of bougainvillea have more flowering buds and more fully blooming flowers, but their growth is slower because they contain more ACC than vertical shoots, and the ACC increases with the number of days of treatment.…”
Section: Discussionsupporting
confidence: 88%
“…However, axillary buds generally developed close to the vegetative buds, and the vertical shoots became less mature than the horizontal and inclined shoots, and so had fewer flowering buds. These observations are consistent with those of Hampson et al (2004), Ito et al (1999), Meilan (1997), and Naor et al (2003). Inclined shoots of bougainvillea have more flowering buds and more fully blooming flowers, but their growth is slower because they contain more ACC than vertical shoots, and the ACC increases with the number of days of treatment.…”
Section: Discussionsupporting
confidence: 88%
“…In both warm and cool areas they will break before the vegetative buds which have a higher chilling requirement (Erez and Couvillon 1987;Naor et al 2003). This was evident in our study, and can explain the differences in BBP observed in the warm area, as all of the terminal BBP 'Granny Smith' axes were terminated by a reproductive bud while 87% of the lateral BBP axes were terminated by a vegetative bud (Table 4).…”
Section: Bud Type In Terminal and Lateral Positions And Bbpsupporting
confidence: 62%
“…Reproductive buds have a lower chilling requirement than vegetative buds in both apple (Naor et al 2003) and peach (Erez and Couvillon 1987). In both warm and cool areas they will break before the vegetative buds which have a higher chilling requirement (Erez and Couvillon 1987;Naor et al 2003).…”
Section: Bud Type In Terminal and Lateral Positions And Bbpmentioning
confidence: 99%
“…firstly endodormancy: the deepest state of dormancy, in which bud burst is prevented by endogenous factors specific to the meristem. The strength of endodormancy increases from the end of summer, throughout the fall, generally peaking somewhere between the end of October and the end of November in the northern hemisphere depending on the species and the climatic conditions prevailing during the fall [4]. A dormancy breaking test, or forcing test, is the method of choice for assessing the depth of endodormancy in trees [5].…”
Section: Introductionmentioning
confidence: 99%